Potential of agroforestry systems in preserving Europe’s soil productivity in lowland and highland landscapes by limiting soil erosion by surface runoff - Wawer, Rafał; Koza, Piotr; Borek, Robert; Gliga, Adrian-Eugen; Ghaley, Bhim Bahadur; Xu, Ying; Smith, Jo; Smith, Laurence; Șandor, Mignon; Pisanelli, Andrea; Augusti, Angela; Russo, Giuseppe; et al. (Polish Journal of Agronomy, 2021)
Over the past half-century, an expansion of agriculture on lands is observed, followed with increased intensification through larger fields of monoculture crops and application of high level of inputs, that icreases the pressures agriculture sets upon the environment. Raising awareness of consumers and environmentalists led to the promotion of several alternative farming practices, including integrated food and non-food systems (IFNS). Here we explore the potential of different kinds of IFNS systems in delivering environmental benefits, focusing on preserving soil functions as the form of land use limiting the loos of soil by water erosion. Six successfully implemented IFNS systems located in UK, Poland, Italy, Denmark and Romania, were taken as a baseline to investigate their potential impact onto lowering soil loss by water erosion in their respective NUTS3 regions, when they would be applied widely on a regional scale. The results of analyses performed within GIS systems based upon European datasets revealed, that altogether the highest potential of limiting the area of soil erosion exceeding 0,5 Mg ha-1y-1 by an IFNS existing in a particular NUTS is observed in Romania, where 531km2 may be protected effectively with exiting silvopastoral system, while applied in a longer term on non-pastoral land cover classes it could provide effective protection for another 1362 km2. Second largest influence can be achieved in Polish NUTS region, where 125 km2 may be taken into protection directly and an another 1140 km2 may be transformed into agroforestry systems to lower the risk of soil erosion by water. In all investigated regions, a wide introduction of IFNS, that are already proven to be economically successful, would decrease soil loss considerably on existing land cover classes similar to IFNS systems covering 4927km2, while potentially on all agricultural land up to 8854km2.